«FOR BETTER - FOR WORSE»: AN UNKNOWN AUTODOCUMENTARY PROSE - Калашнікова, Ольга (SWorldJournal, 2024)
The article deals with the memoirs of the beginning of the twentieth century unknown in Ukraine and in other post-Soviet countries: “The Autobiography of Vladimir Mouravieff-Apostol-Korobyine”, supplementing existing ideas not only about the turbulent era